DETECTION OF ESCHERICHIA COLI IN CHILDREN STOOL WITH DIARRHEA PATIENTS USING CULTURE AND POLYMERASE CHAIN REACTION METHOD - Lokita Purnamasari; Muh Nasrum Massi; Ahyar Ahmad (Faculty of Medicine, Hasanuddin University., 2017)
ABSTRACT Introduction : Diarrheal diseases are a serious issue on health in developing countries and the liquid cause’s morbidity and mortality in children that cause the diarrhea pathogenic bacte- ria including Escherichia coli. This research aims to detect E. coli in stool diarrhea patient of the child with culture method and Polymerase Chain Reaction. Methods : This research is descriptive research design with cross-sectional approach. The sampling was collected from some public health centers namely Pampang, Barabarayya, Antang Perumnas, Tamangapa public health centers. Specimen testing process was conducted at Microbiology laboratory of the Teaching Hospital University of Hasanuddin to identify E. coli bacterium with the culture and to detect eae gene and bfp with PCR technique. Results : The results indicate that from50 samples, there are 15 samples (30%) of samples positively detection E. coli using culture method and PCR test using eae and bfp primer found 20 (40%) and 1 sample (2%) positive enteropathogen E. coli. Conclusion : PCR methods indicated the result of E. coli bacteria results faster and more accurate that other culture methods. Keywords : Diarrhea, Escherichia coli, Polymerase Chain Reaction